Analysis of the hexanucleotide repeat expansion and founder haplotype at C9ORF72 in an Irish psychosis case-control sample. - MORRIS, DEREK; BRADLEY, DANIEL; DONOHOE, GARY; GILL, MICHAEL; CORVIN, AIDEN; FAHEY, CIARA; HARDIMAN, ORLA; MCLAUGHLIN, RUSSELL (My University, 2014)
The hexonucleotide repeat expansion 'GGGGCC' at the C9ORF72 gene has been strongly linked with amyotrophic lateral sclerosis and frontotemporal dementia. There is some evidence for clinical and genetic overlap between frontotemporal dementia and schizophrenia. Here, we genotyped the repeat at C9ORF72 in a large Irish psychosis case-control sample (n = 2477). We found no carriers of >30 repeats. We found 7 samples with >22 repeats, 2 schizophrenia cases and 5 controls, but overall we observed no difference in the distribution of the repeat between our case and control samples. By using genome-wide association data to phase haplotypes at this gene, we investigated if carriers of the repeat expansion arose from a single common founder. All samples that carry 17 or more repeats also carry the founder haplotype and overall there is a very strong correlation between repeat length and the founder haplotype (Spearman rho = 0.714, p < 0.001). Our study provides further evidence to bolster the claim that carriers of the repeat expansion at C9ORF72 arose from a single common founder
PUBLISHED
Keywords: schizophrenia; Genes & Society; Neuroscience